Analisis Pengaruh Segmenting Targeting Positioning Terhadap Minat Beli Ulang Konsumen Produk Teh Tambi Di Wonosobo Jawa Tengah - Nabila Cintya Iswara; Budiarto Budiarto; Antik Suprihanti (Agrisociabus, 2023)
Increasing competition between companies requires companies to improve their marketing strategies. One way is to know in advance the characteristics of consumers so that companies can find out the factors that influence consumers in repurchasing a product. In this case the company can use segmenting, targeting, positioning strategies. Therefore, this study aims to identify the segmenting, targeting, and positioning of Tambi Cap Petruk black tea products and analyze the effect of segmenting, targeting and positioning on the repurchase interest of PT Perkebunan Tambi black tea products. The method used is descriptive research method with the implementation method, namely the survey method. The results of the analysis show that: (1) Tambi Cap Petruk's black tea product segmentation is consumers aged 17-60 years and the majority of consumers are women. Cap Petruk's targeting black tea products are consumers who prioritize quality and affordable prices. Positioning or consumer perceptions of Tambi Cap Petruk black tea products are products with affordable prices, easily recognizable logos or packaging and product quality. (2) Segmenting targeting positioning affects buying interest in Tambi Cap Petruk black tea products.Keywords: Segmenting; Targeting; Positioning; Consumer’s Repurchase Interest; Tambi Cap Petruk Black Tea